The Effect of Emotional Writing on Academic Stress among Psychology Students - Intan Islamia; Meliana Sari Pasaribu; Rauzatul Umaina; Indriani; Nurhidayah; Yuni Maulana (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
Academic stress has become a common problem among university students due to various challenges in adapting to new roles and academic environments. This study aimed to examine the effect of emotional writing on reducing academic stress among students. The research employed a pretest–posttest control group design involving 20 students from Universitas Malikussaleh. Participants in the experimental group engaged in emotional writing activities, while the control group did not receive any treatment. Data were analyzed using a paired samples t-test to determine the effectiveness of the intervention. The analysis showed that the Sig. (2-tailed) value was greater than 0.05 (p = 0.181), indicating no significant difference between pretest and posttest scores in the experimental group. These findings suggest that emotional writing, in this study’s context, did not significantly reduce academic stress. However, this research contributes to understanding the complexity of stress-reduction interventions and highlights the need for further exploration of individual differences and contextual factors influencing emotional writing outcomes.